2006
DOI: 10.1029/2005jc003136
|View full text |Cite
|
Sign up to set email alerts
|

Variability of ocean heat uptake: Reconciling observations and models

Abstract: [1] This study examines the temporal variability of ocean heat uptake in observations and in climate models. Previous work suggests that coupled Atmosphere-Ocean General Circulation Models (A-OGCMs) may have underestimated the observed natural variability of ocean heat content, particularly on decadal and longer timescales. To address this issue, we rely on observed estimates of heat content from the 2004 World Ocean Atlas (available at http://www.nodc.noaa.gov/OC5/indprod.html, hereinafter referred to as WOA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
320
2
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(346 citation statements)
references
References 29 publications
21
320
2
1
Order By: Relevance
“…In our analysis, cutting off the heavy tail required (i) neglecting model structural uncertainty, (ii) a reduction of the aerosol forcing uncertainty to negligible levels, and (iii) reduced uncertainty in oceanic heat uptake. Our analysis suggests that one promising avenue to decide whether the true climate sensitivity is indeed located in the heavy upper tail of current estimates is through improving the skill of the existing ocean observation system to estimate the anthropogenic heat uptake [AchutaRao et al, 2006;Levitus et al, 2005]. The skewness of the climate sensitivity estimate in our analysis hinges critically on the observation error of the oceanic heat content observations: reducing the uncertainty about the oceanic heat uptake shortens the upper tail of the resulting climate sensitivity estimates (Figure 2e).…”
Section: Discussionmentioning
confidence: 99%
“…In our analysis, cutting off the heavy tail required (i) neglecting model structural uncertainty, (ii) a reduction of the aerosol forcing uncertainty to negligible levels, and (iii) reduced uncertainty in oceanic heat uptake. Our analysis suggests that one promising avenue to decide whether the true climate sensitivity is indeed located in the heavy upper tail of current estimates is through improving the skill of the existing ocean observation system to estimate the anthropogenic heat uptake [AchutaRao et al, 2006;Levitus et al, 2005]. The skewness of the climate sensitivity estimate in our analysis hinges critically on the observation error of the oceanic heat content observations: reducing the uncertainty about the oceanic heat uptake shortens the upper tail of the resulting climate sensitivity estimates (Figure 2e).…”
Section: Discussionmentioning
confidence: 99%
“…and AchutaRao et al (2006) instead sampled models to mimic the Levitus et al (2001) calculation and found large discrepancies between global and hemispheric averages, including, in the former, sign reversals [somewhat in conflict with the results of Barnett et al (2001)]. Harrison and Carson (2007) discuss the great difficulties in inferring global upper ocean averages from the data after 1950 and call attention to the need for far better understanding of the accuracies of quoted subglobal averages.…”
Section: ) Lower Bounds On the Sampling Errorsmentioning
confidence: 99%
“…Según AchutaRao et al 2006, los cambios en la capacidad del océano para absorber calor son una fuente de incertidumbre en las predicciones de modelos acoplados (atmósfera-océano), que se vuelve particularmente relevante en escalas decadales o mayores. En general, la importancia de la variabilidad interna se incrementa conforme la escala espacial y temporal se reduce (Hawkins & Sutton 2009).…”
Section: Discussionunclassified